A Devastating Chest Injury: A Case Report - Bikram Keshari Kar; Sudarshan Behera; Nitin Kashyap; Rudra Narayan Dash; Rakesh Dhaka (Journal of Orthopaedic Case Reports)
Introduction: Sternal fractures, although uncommon, pose significant clinical challenges due to potential complicationssuch as respiratory compromise and chest wall instability. Prompt diagnosis and appropriate management are crucial to reduce morbidity. Case Report: We report a case of a 43-year-old male who sustained displaced sternal and rib fractures following a road traffic accident. A midline incision allowed open reduction and internal fixation using a 3.5 mm locking reconstruction plate for the sternum and a 2 mm plate for the rib. Postoperative recovery was uneventful, with significant pain relief and improved respiratory function. Conclusion: This case reinforces the importance of early surgical intervention in unstable sternal fractures. Locking plate fixation offers superior biomechanical stability, faster healing, and fewer complications compared to conservative management or traditional wiring techniques.